Предмет: Математика,
автор: Akachiya1
решиье уравнение (0,7х-2,1)-(0,5-2х)=0,9(3х-1)+0,1.
Ответы
Автор ответа:
0
(0.7х - 2.1) - (0.5 - 2х) = 0.9(3х - 1) + 0.1
0.7х - 2.1 - 0.5 + 2х = 2.7х - 0.9 + 0.1
2.7х - 2.6 = 2.7х - 0.8
2.6 ≠ 0.8
нет решения.
0.7х - 2.1 - 0.5 + 2х = 2.7х - 0.9 + 0.1
2.7х - 2.6 = 2.7х - 0.8
2.6 ≠ 0.8
нет решения.
Похожие вопросы
Предмет: Алгебра,
автор: u3TGRAFi
Предмет: Физика,
автор: sergeylivanov
Предмет: Алгебра,
автор: Аноним
Предмет: Биология,
автор: Бедуин11
Предмет: Математика,
автор: 89288177323